Study on the Contrast between Local Characteristic-scale Decomposition and Local Mean Decomposition - Cui Weicheng; Li Wei; Meng Fanlei; Liu Linmi (Jixie chuandong)
The Local Characteristic-scale Decomposition（ LCD） and the Local Mean Decomposition（ LMD） are two kinds of effective adaptive time-frequency analysis methods which widely used in the field of rotating machinery fault diagnosis. In order to compare the difference of calculation process and the performance of them,aiming at the acquiring of mean curve and decomposition termination conditions,the comparative research are carried out. The deficiencies of LMD in the mean point definition,interpolation method and pure frequency modulation standards are pointed out. Through the simulation signal and the bearing inner ring fault vibration signal analysis,the superiority of LCD is verified,but the part of the mind of LMD can also provide reference for the LCD.